Mercy Street : a novel - Haigh, Jennifer, 1968- (Ecco, an imprint of HarperCollinsPublishers, 2022)
"The highly anticipated new novel by acclaimed New York Times bestselling author Jennifer Haigh-"a gifted chronicler of the human condition" (Washington Post Book World)-is a tense, riveting story about the disparate lives that intersect at a woman's clinic in Boston"--